The influence of submarine hydrothermal systems on seawater sulfate. (1st March 2023) - Hughes, Eleanor R.; Waldeck, Anna R.; Moriarty, Sarah N.; Jamieson, John W.; Martin, Andrew J.; Scheuermann, Peter P.; Syverson, Drew D.; Seyfried, William E.; Reeves, Eoghan P.; Johnston, David T.
Abstract: Seawater sulfate is a major carrier of oxidizing capacity and influences the redox budget of the Earth's surface on geologic timescales. Records of oxygen and sulfur isotopes in seawater sulfate are used to track changes in sulfate cycling through geologic time. Interpretations of these records are typically based on models that describe the seawater sulfate reservoir as a mass balance between microbial, riverine and sedimentary sulfate fluxes. Here, we investigate the influence of hydrothermal sulfate cycling, which remains an unconstrained but potentially significant additional flux in this mass balance. We find that anhydrite (CaSO4 ) from eight submarine hydrothermal vent fields is consistently offset from seawater sulfate in δ 18 O but not Δ ' 17 O or δ 34 S. Experiments at hydrothermal pressure–temperature conditions indicate that this δ 18 O offset is driven by oxygen isotope exchange between sulfate and hydrothermal H2 O at high temperature. An updated isotope mass balance model shows that a flux of hydrothermal sulfate into seawater, derived from retrograde dissolution of hydrothermal anhydrite, could cause high-temperature oxygen isotope exchange to buffer seawater sulfate δ 18 O and Δ ' 17 O by as much as 25%. Hydrothermal sulfate preserved in the Troodos Ophiolite (Cretaceous) also records a δ 18 O and Δ ' 17 O signal of high-temperature oxygen isotope exchange, supporting the conclusion that geologic records of seawater sulfate oxygen isotopes may include a hydrothermal component.